2013
DOI: 10.1038/ejcn.2013.167
|View full text |Cite
|
Sign up to set email alerts
|

Associations of serum n-3 and n-6 polyunsaturated fatty acids with echocardiographic measures among older adults: the Hoorn Study

Abstract: This study found no strong evidence of longitudinal associations of eicosapentaenoic acid and docosahexaenoic acid with echocardiographic measures, however, lower concentrations of alpha-linolenic acid and linoleic acid were associated with decreased LVEF. These results provide evidence for a potential protective role of alpha-linolenic acid and linoleic acid in relation to systolic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…First, circulating fatty acids expressed as proportions better reflect dietary intake than when expressed as concentrations, particularly for PUFA (2) . This is supported by data from our Hoorn (4) and Cohort Study on Diabetes and Atherosclerosis Maastricht (CODAM) (5) cohorts. In 1171 subjects, intakes of dietary fatty acids were measured by a FFQ and circulating fatty acids by GLC.…”
supporting
confidence: 58%
“…First, circulating fatty acids expressed as proportions better reflect dietary intake than when expressed as concentrations, particularly for PUFA (2) . This is supported by data from our Hoorn (4) and Cohort Study on Diabetes and Atherosclerosis Maastricht (CODAM) (5) cohorts. In 1171 subjects, intakes of dietary fatty acids were measured by a FFQ and circulating fatty acids by GLC.…”
supporting
confidence: 58%
“…Because walnuts are rich in alpha-linolenic acid (ALA), melatonin, magnesium, and antioxidants, it is biologically plausible that walnut consumption would promote better heart structure and function. In 336 older white adults enrolled in the Hoorn study, higher serum ALA was related to higher left ventricular ejection fraction and lower left ventricular mass; notably, serum eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) were not related to either cardiac measure [13]. In the NHLBI Family Heart Study participants, dietary ALA intake was inversely related to lower odds of CAD, a known risk factor for HF [14].…”
Section: Introductionmentioning
confidence: 99%
“…This may cause changes in fatty acid concentration and pattern of fatty acids of platelet membranes, and eicosanoids produced from arachidonic acid promote inflammatory and prothrombotic activities. However, dietary intake of arachidonic acid does not appear to be related to the risk of stroke (59) and the association of dietary or circulating arachidonic acid with CHD is yet unclear (60)(61)(62) . More recently, US studies observed that CVD patients with higher concentrations of trimethylamine-N-oxide (TMAO) have a higher risk for major adverse cardiovascular events such as death, myocardial infarction or stroke than patients with low TMAO concentrations (63) .…”
Section: Cvdmentioning
confidence: 99%